As representações sociais da dança no contexto da Educação Física Escolar - Capri, Fabíola Schiebelbein (2010)
Considering dance as one of the body movement culture manifestations of the subject of Physical Education (PE), the current study had as objective the analysis of the dance in the context of Physical Education in School (PES) trying to unveal which social representations students and teachers have about dancing in two (02) Municipal Public Schools and two (02) Private Schools in the city of Ponta Grossa – PR. One research of qualitative nature, which data collection was obtained in the months of September to December of 2008, through follow up and systemic observation of PE classes in 4th grades of Junior High School. As data collection instrument, specific questionnaires were given to teachers and students belonging to the sample of the research, composed by five (05) teachers working currently in Junior High School and approximately three hundred thirty one (331) students of both genders who are between nine (09) and ten (10) years old. The results were submitted to analysis of content based on Social Representations Theory (SRT). After the analysis we could verify that some factors as the systematized content insufficiency in the process of initial formation makes the pedagogical actions of the teacher harder, as well as selection of content by teachers merely by affinity,contribute to the negligence of dancing classes in PE, however the central representation that teachers have in dancing is strongly connected to rehearsals to parties and celebration dates in school´s context. The data collected by the analysis of answered questionnaires by students showed dance strongly represented by pleasure, connected to musical taste and mainly, that students from both genders have positive expectations in relation to dancing and are able to take part in PE when dancing knowledge is applied